2021
DOI: 10.3390/genes12111832
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Exercise-Induced Secreted Protein Acidic and Rich in Cysteine Expression as a Molecular Tool to Optimize Personalized Medicine

Abstract: The numerous exercise benefits for health as well as applications for diseases has lead to exercise being prescribed in many pathological conditions. Secreted protein acidic and rich in cysteine (SPARC) gene expression is stimulated by exercise and SPARC has been suggested as a molecular mediator of exercise. Therefore, we suggest using this property for personalized medicine. This can be achieved by prescribing the exercise with a pattern (duration, intensity, etc.) that corresponds to the optimum SPARC/Sparc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 102 publications
0
9
0
Order By: Relevance
“…In addition, the population selected in the dataset for clinical pathological data statistics and survival prognosis analysis may exhibit regional or genetic differences and certain differences in human physique and living environment are likely to be present. Increases in the serum levels of SPARC may occur as part of biological functions and processes such as tumors and obesity; of note, SPARC expression levels were upregulated in the lung during hypoxia induction in a mouse model, and the hypoxia-inducible factor 2A signaling pathway induces SPARC expression, which in turn has an effect on proliferation and apoptosis of tumor cells in humans (59)(60)(61). It has also been indicated that the SPARC signaling pathway induces albumin-bound paclitaxel, which enhances initial chemoresistance of patients with lung cancer and this may also be used to optimize individual gene therapy regimens, which are important for mechanistic studies, animal models and clinical treatment evaluation in NSCLC (62).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the population selected in the dataset for clinical pathological data statistics and survival prognosis analysis may exhibit regional or genetic differences and certain differences in human physique and living environment are likely to be present. Increases in the serum levels of SPARC may occur as part of biological functions and processes such as tumors and obesity; of note, SPARC expression levels were upregulated in the lung during hypoxia induction in a mouse model, and the hypoxia-inducible factor 2A signaling pathway induces SPARC expression, which in turn has an effect on proliferation and apoptosis of tumor cells in humans (59)(60)(61). It has also been indicated that the SPARC signaling pathway induces albumin-bound paclitaxel, which enhances initial chemoresistance of patients with lung cancer and this may also be used to optimize individual gene therapy regimens, which are important for mechanistic studies, animal models and clinical treatment evaluation in NSCLC (62).…”
Section: Discussionmentioning
confidence: 99%
“…These evidences add up on those of functional genomics [ 78 , 79 , 80 , 81 ] as illustrated by the secreted protein acidic and rich in cysteine (SPARC). Indeed, SPARC expression changes during obesity [ 82 ] and with ageing [ 83 ] and Sparc/SPARC represents an exercise-induced gene upon which exercise-induced muscle phenotype changes would depend [ 84 , 85 ]. In addition, SPARC is involved in diverse biological activities [ 86 ] related to those described above in the context of obesity, ageing, and exercise.…”
Section: Biological Similarities Between Ageing and Obesitymentioning
confidence: 99%
“…SPARC serum levels also increase with exercise [9], both in humans and in mice [10]. We have suggested that the exercise-induced muscle phenotype changes are SPARC-dependent [11], and exercise-induced Sparc expression could be an indicator of the therapeutic efficacy of exercise and the response to exercise [12]. In addition, adding SPARC to C2C12 (muscle cells) increased their differentiation [13].…”
Section: Introductionmentioning
confidence: 95%